A Regression Analysis of Self-Affirmation and Speaking Anxiety on EFL Students’ Oral Performance: A Mixed-Methods Study in an Indonesian Islamic High School - Hidayatulloh, M. David; Tahir, Muhammad; Bakri, Fitriyani (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study investigates the extent to which self-affirmation and speaking anxiety influence English oral performance among Indonesian EFL senior high school students. Employing a mixed-methods explanatory sequential design, the research involved 30 eleventh-grade students from SMAIT Wahdah Islamiyah Makassar. Quantitative data were collected through validated questionnaires and speaking assessments, followed by in-depth interviews with five selected participants to gain qualitative insights. Multiple regression analysis indicated that neither self-affirmation nor speaking anxiety significantly predicted speaking performance, although anxiety demonstrated a marginally negative trend. Descriptive statistics showed wide variations in both psychological and performance measures. Meanwhile, qualitative findings revealed that self-affirmation contributed to mental readiness and reduced nervousness, while speaking anxiety often impaired fluency and focus during oral tasks. Thematic analysis emphasized that self-affirmation alone was insufficient to improve performance but played a meaningful emotional regulatory role when paired with consistent speaking practice. The study contributes to the limited body of research on psychological interventions in Indonesian EFL classrooms by offering empirical evidence and context-specific insights. It highlights that while self-affirmation may not yield immediate performance gains, its potential as an affective support mechanism remains valuable. This research fills a gap in current literature by exploring how self-affirmation operates in tandem with anxiety within a high-school EFL setting in Indonesia—a context underrepresented in previous studies.